The Game-Based ABC Running Exercise Model for Children Ages 6-12 Years - Maranthika Setyantoko; Widiastuti Widiastuti; Hernawan Hernawan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this study is to produce the game-based ABC running exercise model for children ages 6-12 years by testing the effectiveness of increasing the speed of 30 meters short distance running in athletes aged 6-12 years. The research method used in this study is the research and development method of Borg and Gall by using 10 stages. The research subjects in this study are at the age of 6-12 years of athletic at the athletic club in the Special Region of Yogyakarta. The study begins with a data analysis of requirements, planning, product making, testing, revision and final products. The model feasibility test presents 3 experts consisting of 2 athletic lecturers and 1 national athletic trainer. The effectiveness test model uses a 30 meters speed parameter test involving 40 athletes aged 6-12 years consisting of 2 athletic clubs in Yogyakarta Province. Increasing the running speed of 30 meters shows the significance of t-count = 45.64, db = 19 and p-value = 0.00 < 0.05, for the average N-gain of 56.30, which means that the category of interpretation is "quite effective”. This means that there are significant differences in the 30 meters run speed of athletes before and after being given a training model. It can be concluded that the game-based ABC running exercise model developed is effective enough to increase the running speed of 30 meters in athlete’s ages 6-12 years.